Semiconducting photothermal nanoagonist for remote-controlled specific cancer therapy - Zhen, Xu (2018)
Nanomedicine have shown success in cancer therapy, but the pharmacological actions of most nanomedicine are often nonspecific to cancer cells because of utilization of the therapeutic agents that induce cell apoptosis from inner organelles. We herein report the development of semiconducting photothermal nanoagonists that can remotely and specifically initiate the apoptosis of cancer cells from cell membrane. The organic nanoagonists comprise semiconducting polymer nanoparticles (SPNs) and capsaicin (Cap) as the photothermally responsive nanocarrier and the agonist for activation of transient receptor potential cation channel subfamily V member 1 (TRPV1), respectively. Under multiple NIR laser irradiation at the time scale of seconds, the nanoagonists can repeatedly and locally release Cap to multiply activate TRPV1 channels on the cellular membrane; the cumulative effect is the overinflux of ions in mitochondria followed by the induction of cell apoptosis specifically for TRPV1-postive cancer cells. Multiple transient activation of TRPV1 channels is essential to induce such a cell death both in vitro and in vivo because both free Cap and simple Cap-encapsulated nanoparticles fail to do so. The photothermally triggered release also ensures a high local concentration of the TRPV1 agonist at tumor site, permitting specific cancer cell therapy at a low systemic administration dosage. Our study thus demonstrates the first example of ion-channel-specific and remote-controlled drug-delivery system for cancer cell therapy.